PERLINDUNGAN HUKUM HAK KEKAYAAN INTELEKTUAL DALAM KONTRAK FRANCHISE PRODUK CHEMICAL JOSS CLEAN - Di Angelo Fellest Hyaning Sabda; Zaenal Arifin; Endang Setyowati (Fakultas Hukum, Universitas Semarang, 2025)
This study aims to determine the application of Intellectual Property Rights in the franchise agreement on the Chemical Joss Clean Product Franchise contract and the legal consequences if there is a breach of contract on the Chemical Joss Clean Product Franchise. The innovative and environmentally friendly